Why should the neonatologist give a closer look at the alkaline phosphatase? - Vlad Dima; Roxana-Elena Bohiltea; Raluca Mariana Stanescu; Andreea Avramescu-Calomfirescu; Valentin-Nicolae Varlas; Ana-Maria Davitoiu (Amaltea Medical Publishing House, 2022)
Background. Alkaline phosphatase (ALP) has been intensively studied and proved to be useful in Neonatology. The first condition studied in correlation with increased ALP values was osteopenia of prematurity. In recent years there was an increase interested in correlations between ALP and bilirubin levels. In this article, we want to review the literature to find other benefits of ALP dosing in neonatal patients. Methods. Clinical trials were searched and analyzed by a single individual (via dedicated search engines such as Google Scholar, PubMed, and Scopus). We have included clinical studies from the last 7 years that present statistically significant results regarding the role of ALP dosing in the screening or diagnosis of other neonatal pathologies (jaundice with hyperbilirubinemia, necrotizing enterocolitis, liver dysfunction, renal failure and oncological diseases). Results. After excluding the clinical trials that did not meet the eligibility criteria, 6 clinical trials remained (n = 859). Following the analysis of these studies, correlations were highlighted between high ALP values in the umbilical cord and the need for phototherapy. It was also shown that all newborns with elevated ALP values required treatment for hyperbilirubinemia, as well as being a good predictor of severe jaundice and helping to predict its onset. Also, evidence about the correlation between high values of ALP and prematurity osteopenia was reaffirmed in recent studies. Conclusions. ALP is an easily dosed biomarker that can be successfully used in Neonatology. The existing studies to date encourage the use of ALP as a biomarker especially for the detection of osteopenia of prematurity and for the early detection of newborns who will develop intense forms of jaundice. There are still differences regarding the serum ALP values considered as cut-offs for the diagnosis of various neonatal conditions, but performing multicenter studies on a large number of cases could establish a valid consensus in order to use the same ALP cut-off values in all Neonatology departments.